Analysis and comparisons on carotenoid content between ripe and unripe bunches / Anith Arina Mohd Shahrome - Mohd Shahrome, Anith Arina (Faculty of Plantation and Agrotechnology, 2019)
Elaies Guineensis is the most planted commodity crop in Malaysia. In the year 2017, oil palm sectors contributed to around RM 71.5 billion to the Malaysian economy. However, the current processing method of producing vegetable oil for human consumption will deteriorate the carotene content. Carotenoids are natural chemical compounds that give palm oil its orange-red colour. These compounds are actually good for human health as it can strengthen body immunity system and also act as antioxidant. Carotenoids are abundant in crude palm oil as it can reach 500-700 ppm and the beta carotene found in it will be converted into Vitamin A as it enters body systems. So, the objective of this study was to determine the carotenoid content in ripe and unripe oil palm bunches to make full use of these compounds. The analysis of oil samples was done using Near Infrared Spectroscopy Diode Array (NIRS DA) 1650 machine. Apart from carotenoid content, Deterioration of Bleachability Index (DOBI) and Free Fatty Acid (FFA) content can also be obtained. Stalks were removed from bunches. A total of 1 kg fruitlets were boiled, mesocarps were peeled off and pressed in order to obtain the oil samples. Oil samples were taken to Kempas Laboratory to analyze its content. It is proven that ripe bunches contain the average carotene content of ±968.07 ppm compared to unripe bunches with only ±927.37 ppm. Extraction of this chemicals should be done enormously in order to fulfill the needs of people in the countries that have serious health problems due to the insufficient amount of vitamin A in their bodies.